Study of passive design used in Perak Traditional Malay House (PMTH)to achieve thermal comfort / Husna Liyana Sabaruddin and Ahmad Faiz Hassan Naziri - Sabaruddin, Husna Liyana; Hassan Naziri, Ahmad Faiz (2019)
The purpose of this study is to investigate the application of passive design used in Perak Traditional Malay house (PMTH). The problem statement is the design element used in Perak Traditional Malay house implied the passive design element for thermal comfort. This research is going to identify the passive design element used in the selected PMTH. This research is conducted in various sources such as article, books or by the observation on the design element. Finally, this research gives an experience on how to make a space that will response with passive design element to achieve thermal comfort.